Pengaruh Kepemimpinan Instruksional Kepala Sekolah Terhadap Kinerja Mengajar Guru SMP Negeri Se-Kabupaten Padang Pariaman - Marnur, Wahyuda; Sulastri (Journal of Practice Learning and Educational Development, 2025)
The purpose of this study was to determine the effect of the principal's instructional leadership on the teaching performance of public junior high school teachers in Padang Pariaman Regency. The population in this study was the population in this study were all public junior high school teachers in Padang Pariaman Regency totaling 1,187 with a research sample of 69 people taken based on Cluster Sampling techniques and Stratified Proportional Random Sampling.The data analysis technique used simple linear regression analysis using the SPSS version 29 program. The results showed that there was a positive and significant influence of the principal's instructional leadership on teacher teaching performance from the regression equation Y = 92, 967 + 0.542X, so that the principal's instructional leadership variable partially had a significant effect on teacher teaching performance by 28.5% and 71.5% was influenced by other factors.